2019
DOI: 10.1111/inr.12504
|View full text |Cite
|
Sign up to set email alerts
|

Developing personal sense of risk: a grounded theory in men with hypertension

Abstract: Background For older men with hypertension living in rural areas, non‐adherence to treatment is a common phenomenon. The experience on risk perception of individuals with their condition is recognized as playing a critical role in promoting treatment adherence. However, the experience on risk perception in a cohort of older men with hypertension seems unclear. Aim To develop a theory concerning risk perception experience in a cohort of older men with hypertension from a rural area of Thailand. Methods A ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Thus, their behaviour might be influenced by these individuals, as they may make decisions based partly on others' experiences. Risk perceptions regarding ageing, health, economics, and family are important for older patients, 18 and these perceptions influence their health‐related behaviour, including understanding disease, improving self‐management, 19 and changing healthcare‐seeking behaviour (as necessitated by policy changes) 20 …”
Section: Contextmentioning
confidence: 99%
“…Thus, their behaviour might be influenced by these individuals, as they may make decisions based partly on others' experiences. Risk perceptions regarding ageing, health, economics, and family are important for older patients, 18 and these perceptions influence their health‐related behaviour, including understanding disease, improving self‐management, 19 and changing healthcare‐seeking behaviour (as necessitated by policy changes) 20 …”
Section: Contextmentioning
confidence: 99%
“…Lin L. et al [ 10 ] used grounded theory to analyze the factors that affect farmers’ willingness to sell agricultural products through new media and combined the analysis results to provide suggestions for solving practical problems in agricultural product sales. Seesawang J. et al [ 11 ] used grounded theory to develop a theory about the personal risk perception experience of elderly hypertensive male patients in rural Thailand. Grounded theory combined with the semi-structured interview method has a certain degree of freedom and openness and is able to explore on indicators that are overlooked in current theories.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that individuals who perceive themselves at a higher risk of CVD are more likely to adopt a healthy lifestyle ( 9 , 10 ) or demonstrate a willingness to consider future prevention therapy ( 11 ). In general, knowledge of the widely promoted risk factors for CVD, such as elderly, smoking, being obese, and high blood pressure, may form the basis of an individual's risk perception ( 6 , 12 ). Thus, improving knowledge and risk perception is an integral part of behavioral interventions aimed at reducing the incidence of CVD ( 13 ).…”
Section: Introductionmentioning
confidence: 99%